Revealing the ancient origins of blonde beers: Phylogeography and phylogenetics of cryotolerant fermentative yeast Saccharomyces eubayanus from pre-Hispanic pottery in Northwestern Patagonia, Argentina - Alberto E Pérez; Jacobo Hernandez-Montelongo; Melisa González Flores; María Eugenia Rodríguez; Christian A Lopes; José Luis Lanata (PLoS ONE, 2025)
This study presents an analysis of residuals and the identification of the oldest cryotolerant fermentative yeast Saccharomyces eubayanus, absorbed in the walls of ceramic vessels. The samples were dated between 920 and 750 years before present (BP) from the Meliquina Lake site in northwest Argentine Patagonia. This study provides more solid evidence supporting the hypothesis of a pre-Hispanic development area for fermented beverage production at the southernmost region between −38∘ and −40∘ south latitude on the continent. The isolation and subsequent phylogenetic and phylogeographic analysis of this yeast strain confirm its primitive nature, predating the previously known European hybrids. The associated context and chronology of its use, predating European-Indigenous contact, provide evidence of its management and utilization in native or autochthonous fermentative processes. Subsequently, for reasons still unclear, the strain migrated to Europe, where it hybridized with Old World strains, culminating in the emergence of blonde beers or lager in 16th century Bavaria. The deliberate or unintentional nature of this migration remains speculative, but it underscores the significant role this yeast strain played in the development of one of today’s most popular fermented beverages, which necessitate fermentation at low temperatures.